Copper oxide thin film and nanowire as a barrier in ZnO dye-sensitized solar cells - Phathaitep Raksa (2018)
The ZnO dye-sensitized solar cells (DSSCs) with different photoelectrodes were studied on the effect of CuO layer as a barrier layer toward power conversion characteristics. The structures of DSSCs based on ZnO as a photoelectrode, Eosin-Y as a dye sensitizer, iodine/iodide solution as an electrolyte and Pt/FTO as a counterelectrode. CuO powder, nanowire prepared by oxidation reaction of copper powder and CuO thin film prepared by evaporation copper thin film, were used as a layer on the top of ZnO layer to form blocking layer. The photocurrent, photovoltage and power conversion efficiency characteristics for DSSCs were measured under illumination of simulated sunlight obtained from a solar simulator with the radiant power of 100 mW/cm2. It was found that ZnO DSSCs with CuO thin film exhibited highest current density of 5.10 mA/cm2and highest power conversion efficiency of 0.92% than those of CuO powder and nanowire. The enhancement of the power conversion efficiency can be explained in terms of the retardation of the interfacial recombination dynamics of CuO blocking layer. © 2009 Elsevier B.V.